Relationship between active learning heuristic problem-solving approach and students’ attitude towards mathematics - Wakhata, Robert; Mutarutinya, Védaste; Balimuttajjo, Sudi (Eurasia Journal of Mathematics, Science and Technology Education, 2023)
The study explored the direct relationship between active learning heuristic problem-solving approach and students’ attitude towards mathematics, using linear programming (LP) word tasks. Two instruments were used for data collection: The Attitude towards Mathematics Inventory-Short Form was adapted (with α = .75) as a multidimensional measurement tool, and a validated standardized active learning heuristic problem-solving tool. A quantitative approach with a quasi-experimental pre-test, post-test, and non-equivalent control group study design was adopted. A sample of 608 grade 11 Ugandan students (291 males and 317 female) from eight secondary schools (public and private), four from central Uganda, and the remaining four from eastern Uganda participated. Data were analyzed using PROCESS macro for SPSS (v.4). The results revealed a direct significant positive relationship between active learning heuristic problem solving approach (ALHPSA) and students’ attitude towards solving LP word tasks (ATLPWTs). Thus, the ALHPSA positively and directly impacted on students’ ATLPWTs. The findings can be explained by theoretical, conceptual, and/or psychometric factors. Overall, the results indicate beneficial practical implications that support the theoretical framework for enhancing the learning of mathematics using word problems in Ugandan secondary schools and beyond.
Keywords: Active learning; Attitude; Heuristic problem-solving; Mathematics; Linear programming; Secondary schools